Tunable Structures and Properties of Electrospun Regenerated Silk Fibroin Mats Annealed in Water Vapor at Different Times and Temperatures - Xiangyu Huang (Journal of Nanomaterials, 2014)
Regenerated silk fibroin (SF) mats were fabricated using electrospinning technique, followed by mild water vapor annealing to effectively tune the structures and improve the mechanical properties of the mats at different annealing times and temperatures. The breaking strength and the breaking energy of the mats treated with water vapor at 65°C for 12 h reached 6.0 MPa and 171.7 J/kg, respectively. The conformational transition of the SF mats was significantly influenced by the treating temperature, while the influence of time was comparatively limited. The influence is consistent with the time-temperature equivalent principle and would be helpful for the preparation of water-vapor-annealed silk-based biomaterials for various applications.